2015
DOI: 10.1080/10408398.2013.811212
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nitrate, Nitric Oxide, and Cardiovascular Health

Abstract: Emerging evidence strongly suggests that dietary nitrate, derived in the diet primarily from vegetables, could contribute to cardiovascular health via effects on nitric oxide (NO) status. NO plays an essential role in cardiovascular health. It is produced via the classical L-arginine-NO-synthase pathway and the recently discovered enterosalivary nitrate-nitrite-NO pathway. The discovery of this alternate pathway has highlighted dietary nitrate as a candidate for the cardioprotective effect of a diet rich in fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 181 publications
1
90
0
5
Order By: Relevance
“…Leafy green vegetables are a rich source of dietary nitrate that can be reduced to NO via the entero‐salivary nitrate‐nitrite‐NO pathway . Although significant in the unadjusted analysis, after adjustment for covariates and especially after further adjustment of intake of nonleafy green vegetables, which included allium and cruciferous vegetables, the beneficial effect disappeared.…”
Section: Discussionmentioning
confidence: 92%
“…Leafy green vegetables are a rich source of dietary nitrate that can be reduced to NO via the entero‐salivary nitrate‐nitrite‐NO pathway . Although significant in the unadjusted analysis, after adjustment for covariates and especially after further adjustment of intake of nonleafy green vegetables, which included allium and cruciferous vegetables, the beneficial effect disappeared.…”
Section: Discussionmentioning
confidence: 92%
“…There is a need to determine whether these improvements in risk factors can translate into improved long-term 4 Measured in 1215 participants. 5 Measured in 1106 participants. 6 Measured in 895 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Through this pathway, NO is generated via the sequential reduction of the anions nitrate and nitrite by the facultative anaerobic bacteria on the dorsal surface of the tongue, the acidic environment of the stomach, and a number of endogenous molecules identified as having nitritereducing potential (5). This nitrate-nitrite-NO pathway is independent of NO synthase (NOS) and may be enhanced in instances of hypoxia (6).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous NO produced by NO synthase in endothelial cells mediates vascular dilation and inhibits infiltration of inflammatory cells and platelet aggregation . Increased consumption of inorganic nitrate in green leafy vegetables and beetroot have potential cardiovascular benefits . Recently, a meta‐analysis and several clinical studies have suggested that dietary inorganic nitrate or beetroot juice reduced plasma LDL, and systolic blood pressure, with improved endothelial and cardiac function …”
Section: Introductionmentioning
confidence: 99%